Digital electronics - Green, D. C. (New Delhi : Pearson Education, 1999)
This new edition of Digital Electronics is up-to-date with current devices and includes many practical exercises whilst continuing to provide a comprehensive introduction to the principles of modern digital electronics.
Includes index.
Keywords: Digital electronics